ANALISIS KEBIJAKAN PEMBIAYAAN PENDIDIKAN MENENGAH DI SMA NEGERI 2 KARANGANYAR: DAMPAKNYA TERHADAP AKSES DAN MUTU - Febrianti T. Lestary; Harsono; Sukasno; Suyatmini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study analyzes the implementation of secondary education financing policy through School Operational Assistance (BOS) and Regional Education Operational Assistance (BOPD) programs and their impact on access and quality at SMA Negeri 2 Karanganyar. The research employs a qualitative approach with instrumental case study design, utilizing in-depth interviews with key informants including school principals, finance vice-principals, teachers, and school committee representatives. Data analysis uses thematic analysis with inductive approach to identify patterns and themes related to policy implementation effectiveness. The findings reveal that financing policy implementation achieves 100% coverage for all public schools with National School Principal Numbers (NPSN), successfully eliminating financial barriers through the abolition of Monthly Student Fees (IBPD). The policy demonstrates transformative impact on educational access, particularly for students from economically disadvantaged families, supporting the 13-Year Compulsory Education program and equity principles. Strong positive correlation exists between adequate financing and educational quality achievement, with infrastructure and facilities identified as priority components for allocation. Strategic recommendations include reallocating book purchases from 10% to 5% and increasing infrastructure maintenance allocation from 20% to 25%, implementing priority-based financing model integrated with education quality report cards for enhanced policy effectiveness.